EBV abortive lytic cycle promotes nasopharyngeal carcinoma progression through recruiting monocytes and regulating their directed differentiation. - Xiaoting Xu; Nannan Zhu; Junming Zheng; Yingying Peng; Mu-Sheng Zeng; Kai Deng; Chaohui Duan; Yan Yuan (PLoS Pathogens, 2024)
Epstein-Barr virus (EBV) is associated with several types of human cancer including nasopharyngeal carcinoma (NPC). The activation of EBV to the lytic cycle has been observed in advanced NPC and is believed to contribute to late-stage NPC development. However, how EBV lytic cycle promotes NPC progression remains elusive. Analysis of clinical NPC samples indicated that EBV reactivation and immunosuppression were found in advanced NPC samples, as well as abnormal angiogenesis and invasiveness. To investigate the role of the EBV lytic cycle in tumor development, we established a system that consists of two NPC cell lines, respectively, in EBV abortive lytic cycle and latency. In a comparative analysis using this system, we found that the NPC cell line in EBV abortive lytic cycle exhibited the superior chemotactic capacity to recruit monocytes and polarized their differentiation toward tumor-associated macrophage (TAM)-like phenotype and away from DCs, compared to EBV-negative or EBV-latency NPC cells. EBV-encoded transcription activator ZTA is responsible for regulating monocyte chemotaxis and TAM phenotype by up-regulating the expression of GM-CSF, IL-8, and GRO-α. As a result, TAM induced by EBV abortive lytic cycle promotes NPC angiogenesis, invasion, and migration. Overall, this study elucidated the role of the EBV lytic life cycle in the late development of NPC and revealed a mechanism underlying the ZTA-mediated establishment of the tumor microenvironment (TME) that promotes NPC late-stage progression.